TINGKAT PARTISIPASI MASYARAKAT DALAM PELESTARIAN KAMPUNG KAUMAN SURAKARTA - Rahardian Maulana; Nurini Nurini (TATALOKA, 2019)
Kampung Kauman is located in the center of the city that has a wealth of culture and has a historical potential both in terms of physical environment and in the form of ancient buildings that are still authentic and traditions of society with religious distinctiveness. There are various relics of ancient buildings that are still well maintained, but there are ancient buildings that are not well maintained and not defined as a cultural heritage building so it needs to be preserved so that its authenticity is maintained. Conservation with a bottom up approach is a preservation that involves community participation in every activity. Conservation by involving community participation are considered more effective because it is able to grow a strong sense of belonging. The purpose of this study is to analyze the level of community participation in the conservation of Kampung Kauman as a historic place in the city of Surakarta and know the factors that influence it. Analytical techniques used include descriptive quantitative analysis using cross tabulation method and chi square test. Based on analysis of cross tabulation and chi square test that has been done, internal factors that have relationship with form and level of society participation are gender, education level, and length of stay. While external factors that have a relationship with the shape and level of community participation is the role of the kelurahan, community figure, and paguyuban Batik Kauman.